Effective Time Management for Teaching Effectiveness (2008)
This paper discusses the essence of time management and its positive effect on teaching and subsequently on learning. Samples were selected in two phases of the study viz: a the outset when 31 schools were selected in Ibadan City and after phase one of the study when the most effective teacher-time-manager and the least-effective-teacher-time manager were identified. Thirty students each from these classes were randomly selected and used as the pretest -post test experimental/control groups design to confirm or confound the results of one. Findings include: effective-time management resulted in effective and learning, if teachers were to be effective time managers they must minimise social activities and devote more time preparation, good time management engenders improved Student 'performance etc. Recommendations were that to assist teachers to manage their time better, they should be well remunerated; teachers should reduce their social activities to the barest minimum; they should the business more seriously among others.